3D chiral color prints for anti-counterfeiting. Issue 12 (12th March 2019) - Liu, H. L.; Zhang, Bing; Gao, Tian; Wu, Xijun; Cui, Fayi; Xu, Wei
Abstract : 3D chiral color printing displays a color image under left-handed circular-polarized light, while revealing a different appearance under right-handed light. Abstract : Here we demonstrate a novel anti-counterfeiting method, 3D chiral color printing, which displays a plasmonic color print under left-handed circular polarized (LCP) light, while revealing a different color image under right-handed circular polarized (RCP) light. We employ double-layer arcs as 3D chiral color pixels due to their giant difference of chiroptical response to LCP and RCP illumination. Asymmetric and symmetric plasmon coupling modes are attributed to the origin of LCP and RCP colors, respectively. Through tuning the arc lengths, a wide range of RCP and LCP colors, respectively occupying 32% and 19% of the sRGB space, are achieved. Moreover, an algorithm to hide a covert circular-polarized color image underneath an opposite handed circular-polarized color print is presented. Our 3D chiral color printing has potential applications in optical security and document authentication.